A Study on Digital Democracy Practice: Opportunities and Challenges of e-Health Implementation in Indonesia - Bevaola Kusumasari; Widodo Agus Setianto; Li Li Pang (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
As a developing country, Indonesia faces a crucial issue concerning the provision of health services to the public. The 1998 political reform led to demands for more aspiring and accommodating bureaucratic services being aﬀorded to the public. The political reform brought about bureaucratic reform bearing good governance, wherein one of its forms is the provision of health services through the innovation of an information technology (IT) based service named e-Health. Keeping in mind Indonesia’s characteristics as a developing country, the implementation of IT-based services evokes numerous debates. This study aims to analyze the implementation of e-Health along with the opportunities it has, and the challenges it faces. By using a study case approach on the Surabaya Municipality Health Authority as the initiator and implementer of e-Health, as well as observations and user surveys, the results show that in spite of having been prepared properly with supporting policies, infrastructure, budgeting, dissemination, and operational system, there were still many prevalent obstacles encountered, particularly concerning digital divide, technical diﬃculties, psychological barriers, and cultural issues. Nevertheless, there are numerous opportunities available for refining e-Health implementation, provided there is a political will from the government to improve and enhance the ICT infrastructure, widespread use of mobile devices, involvement of public participation, and equal distribution of service points easily accessible to the public. Strong government commitment also serves as a guarantee for e-Health service program sustainability in Surabaya Municipality.